THE IMPACT OF THE BETTING INDUSTRY ON SPORTS - Ioan TURCU; G.B. BURCEA; D.L. DIACONESCU; M.C.R BARBU; M.C. POPESCU; P. APOSTU (Editura Universitatii Transilvania din Brasov, 2020)
: Sports betting is the oldest form of gambling in the world. In the beginning, it was simply a leisure activity. We are currently talking about a multi-billion-euro deal. The sports betting industry has changed more in 15 years than in the last 50 years. In the 1950s, sports betting began to enter the world and almost nothing changed until the beginning of the 21st century. However, with the onset of the new millennium, online betting has changed the landscape dramatically, and is now developing at a fast pace than ever before. The future is always unpredictable, but we will try to imagine it based on current trends in sports betting. The paper "The impact of the betting industry on sports" aims to present a series of aspects regarding the history of sports games, the types of sports games existing today, a brief highlight of the Romanian sports games market and a short presentation of the positive and negative effects on sports.